High‐density lipoproteins in high resolution: Will proteomics solve the paradox for cardiovascular risk?. Issue 3 (February 2017) - Baig, Ferheen; Joshi, Abhishek; Mayr, Manuel
Abstract : While lipid abnormalities continue to account for over 60% of the population attributable risk for myocardial infarction, the well‐known inverse correlation between plasma high‐density lipoprotein (HDL) cholesterol and cardiovascular risk has failed to deliver clinically useful therapeutic interventions. Thus, there is an unmet need to better understand the function of different HDL particles. Targeted, high‐resolution lipoproteomics provides an innovative approach to studying the kinetics of HDL particles. In this commentary, we discuss the development of an informatics platform for increased throughput and highlight how this approach delivers the potential for novel, hybrid instrument technologies to inform clinical dyslipidemia studies.